PEMBUATAN PETA SITUASI DUSUN CUNGKRUNGAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , BERIZKA ARDANIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report is to explain about measuring and mapping the earth's surface to generate spatial data information. Spatial data include spot height and planimetric detail obtained from measurements of the earth's surface which is processed into a map. The method used is the making of the map control framework a measurement framework of horizontal control and vertical control framework, measurement of planimetric detail and a high point, as well as digital mapping. The results obtained were present situation map spatial data Earth's surface at cungkrungan hamlet,village outs,freshman,districts, Klaten district, Central Java province in the system using a scale of 1:500 projection UTM (Universal Transverse Mercator).